SCN5A mutation type and a genetic risk score associate variably with Brugada Syndrome Phenotype in SCN5A families - Wijeyeratne, Yanushi; Tanck, Michael W.; Mizusawa, Yuka; Batchvarov, Velislav; Barc, Julien; Crotti, Lia; Bos, J. Martijn; Tester, David J.; Muir, Alison; Veltmann, Christian; Ohno, Seiko; Page, Stephen P.; et al. (Circulation. Genomic and precision medicine, 2020)
Background: - Brugada syndrome (BrS) is characterized by the type 1 Brugada ECG pattern. Pathogenic rare variants in SCN5A (mutations) are identified in 20% of BrS families in whom incomplete penetrance and genotype-negative phenotype-positive individuals are observed. E1784K-SCN5A is the most common SCN5A mutation identified. We determined the association of a BrS genetic risk score (BrS-GRS) and SCN5A mutation type on BrS phenotype in BrS families with SCN5A mutations. - Methods: - Subjects with a spontaneous type 1 pattern or positive/negative drug challenge from cohorts harboring SCN5A mutations were recruited from 16 centers (n=312). Single nucleotide polymorphisms previously associated with BrS at genome-wide significance were studied in both cohorts: rs11708996, rs10428132, and rs9388451. An additive linear genetic model for the BrS-GRS was assumed (6 single nucleotide polymorphism risk alleles). - Results: - In the total population (n=312), BrS-GRS ≥4 risk alleles yielded an odds ratio of 4.15 for BrS phenotype ([95% CI, 1.45-11.85]; P=0.0078). Among SCN5A-positive individuals (n=258), BrS-GRS ≥4 risk alleles yielded an odds ratio of 2.35 ([95% CI, 0.89-6.22]; P=0.0846). In SCN5A-negative relatives (n=54), BrS-GRS ≥4 alleles yielded an odds ratio of 22.29 ([95% CI, 1.84-269.30]; P=0.0146). Among E1784K-SCN5A positive family members (n=79), hosting ≥4 risk alleles gave an odds ratio=5.12 ([95% CI, 1.93-13.62]; P=0.0011). - Conclusions: - Common genetic variation is associated with variable expressivity of BrS phenotype in SCN5A families, explaining in part incomplete penetrance and genotype-negative phenotype-positive individuals. SCN5A mutation genotype and a BrS-GRS associate with BrS phenotype, but the strength of association varies according to presence of a SCN5A mutation and severity of loss of function.
Gesehen am 18.07.2024